Round-up of GHSA Steering Group and Action Packages in 2015 - GHSA Steering Group Secretariat (Osong Public Health Res Perspect, 2015)
All Global Health Security Agenda (GHSA) Steering Group Members remain strongly committed to accelerating measurable progress and implementing concrete commitments toward a world safe and secure from infectious disease threats, recognizing the devastation of the Ebola epidemic and the clear interdependence of health in the 21(st) century. All GHSA Steering Group members reinforced that GHSA is supportive of International Health Regulations implementation, as well as components of other global health security frameworks such as the World Organization for Animal Health Performance of Veterinary Services pathway. The GHSA will continue to focus on multilateral engagement. The GHSA Steering Group is committed to engaging non-state actors and agreed to discuss next steps toward engaging the private sector.